2005
DOI: 10.1007/s11092-006-9002-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Student Evaluations of Teaching Quality: The Contributions of Class Attendance

Abstract: Institutions of higher learning employ compulsory attendance policies with the expectation that these mandates enhance students' academic performance and perceptions of course quality. However, numerous empirical investigations demonstrate equivocal and often contradictory findings regarding the relationship between attendance and various markers of student achievement. The present investigation extends this research by exploring the utility of student ratings of the need to attend class in predicting their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…At the extremes (as seen in Table 4), instructors assigned to large courses (>100 students) had aggregate average SET scores (M 5 3.81, SD 5 0.44) that were more than one-half point lower than those of their peers assigned to small courses (< 20 students; M 5 4.32, SD 5 0.46). Overall, the results reported in this article are in broad agreement with the majority of the cited literature (Ellis et al, 2003;Burns & Ludlow, 2005;Westerlund, 2008;Chapman & Ludlow, 2010;Ragan & Walia, 2010). Another significant variable that affected aggregate SET scores was course level.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the extremes (as seen in Table 4), instructors assigned to large courses (>100 students) had aggregate average SET scores (M 5 3.81, SD 5 0.44) that were more than one-half point lower than those of their peers assigned to small courses (< 20 students; M 5 4.32, SD 5 0.46). Overall, the results reported in this article are in broad agreement with the majority of the cited literature (Ellis et al, 2003;Burns & Ludlow, 2005;Westerlund, 2008;Chapman & Ludlow, 2010;Ragan & Walia, 2010). Another significant variable that affected aggregate SET scores was course level.…”
Section: Discussionsupporting
confidence: 88%
“…When class size is treated as a categorical value (e.g., large, medium, small), larger courses have lower SETs (Lovell & Haner, 1955;Hippensteel & Martin, 2005;Ragan & Walia, 2010). A significant negative correlation occurs when class size and SET are compared directly (Franklin et al, 1991;Ellis, Burke, Lomire, & McCormack, 2003;Burns & Ludlow, 2005;Westerlund, 2008;Chapman & Ludlow, 2010;Ragan & Walia, 2010).…”
Section: Course Characteristicsmentioning
confidence: 99%
“…On the downside, female students have less selfconfidence (Sadler- Smith, 1996) are more anxious and have a higher fear of failure (Osbourne, 2001). These findings are important in terms of the CEQS Model as application to study and course participation has been found to significantly affect student perceptions of both teaching and course quality (Burns & Ludlow, 2006;Voelkl, 1995). Although there have been mixed findings in relation to gender and student evaluations, Basow, Phelan and Capotosto (2006) found that male students tend to rate female faculty lower than female students and this is supported by earlier findings of Centra and Gaubatz (2000).…”
Section: Hypotheses Developmentmentioning
confidence: 59%
“…There are a total of 35 variables associated with each class record. When used in combination, these administrative, student, and instructor variables provide a complex picture of the teaching and learning environment within which a class was taught, and they may be used to examine, and test, a variety of pedagogically meaningful relationships (Burns and Ludlow 2005;Chapman and Ludlow 2010;Ludlow 1996Ludlow , 2002Ludlow , 2005Ludlow and Alvarez-Salvat 2001). Although the unit of analysis is the class, interpretations of results are deductions (based on the previously cited research, personal teaching experience, and conversations with students) about instructor behaviors, classroom learning conditions, and what students may have been considering when they completed the evaluations.…”
Section: Data Descriptionmentioning
confidence: 99%